A carbazole-based spherical microporous polymer for the solid-phase extraction of chlorophenols from water and honey samples. (1st January 2023) - Guo, Yaxing; Wang, Juntao; Hao, Lin; Liu, Weihua; Yang, Xiumin; Wu, Qiuhua; Wang, Zhi
Highlights: New carbazole-based spherical micropore polymer (Car-POP) was synthesized. The Car-POP exhibited a high adsorption capability for chlorophenols (CPs). CPs were efficiently extracted with it as SPE adsorbent before HPLC detection. The developed method was suitable for the determination of CPs in honey samples. Abstract: A new carbazole-based spherical microporous polymer (Car-BDA-POP) was fabricated by employing 4, 4′-biphenyldicarboxaldehyde (BDA) and carbazole as monomers via a one-step and non-metal catalyst synthetic approach. It was then explored as an adsorbent for solid-phase extraction (SPE) of some chlorophenols (CPs). Under the optimized extraction conditions, the established Car-BDA-POP-based SPE coupled with high-performance liquid chromatography ultraviolet detection showed good linearity in the concentration range of 0.1–200 ng mL −1 for water samples and 5.0–800 ng g −1 for honey samples with the determination coefficients ( r 2 ) ≥ 0.9995 for the analytes. The limits of detection (S/N = 3) for the analytes were in the range of 0.03–0.06 ng mL −1 for water samples and 1.50–2.50 ng g −1 for honey samples. The method recoveries varied from 80.0 % to 116 % in spiked real samples, with the relative standard deviations less than 9.6 %. In addition, the possible adsorption mechanism, adsorption kinetics, and adsorption isotherms were also investigated.